PENGARUH CAPITAL INTENSITY, SALES GROWTH, DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP TAX AVOIDANCE : Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang Terdaftar di BEI - Salma Rismawati; Sri Nitta Crissiana Wirya Atmaja (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
The study objective was to determine the effect of capital intensity, sales growth and disclosure of corporate social responsibility on tax avoidance. This study was conducted at manufacturing companies in the food and beverage sector on the Indonesia Stock Exchange for the period 2017-2021 with a total sampel of 17 companies. This type of study is quantitative with associative methods and uses a purposive sampling technique, so that a sample of 74 data is obtained for research. Data analysis in this study used the Eviews 9 application with a panel data regression model. The results of this study indicate that simultaneously capital intensity, sales growth and disclosure of corporate social responsibility have an effect on tax avoidance, while partially capital intensity has no effect on tax avoidance, partially sales growth has an effect on tax avoidance, and partially disclosure of corporate social responsibility no effect on tax avoidance